Modulation of B cell activation by extracellular vesicles and potential alteration of this pathway in patients with rheumatoid arthritis (2022)
ABSTRACT: Background: Extracellular vesicles are involved in the intercellular communication of the immune system. In rheumatoid arthritis (RA), these structures are considered a source of autoantigens that drive proinflammatory responses of innate immune cells. A high concentration of circulating medium/large size extracellular vesicles (m/lEVs) and m/lEVs forming immune complexes (m/lEV-ICs) have been associated with disease activity and systemic inflammation in patients with RA. B cells are central components of RA immunopathology because of their involvement in the production of autoantibodies, antigen presentation, and cytokine production. However, the effect of m/lEVs on B cell function in the context of RA and other autoimmune diseases remains unknown. Methods: We evaluated the effect of m/lEVs obtained from healthy donors (HD) and patients with RA on B cell responses in vitro. In addition, we evaluated the effect of pre-exposition of monocyte-derived macrophages (MDM) to m/lEVs on activation of autologous B cells from HD and patients. Results: The presence of m/lEVs reduced the frequency of CD69+ and CD86+ B cells from HD activated by an agonist of antigen receptor. This regulation of the B cell activation markers by m/lEVs was partially dependent on phosphatidylserine binging. These m/lEVs also reduced the proliferation, calcium mobilization, and global phosphorylation of tyrosine. Similar responses were observed in B cells from patients with RA. However, the presence of m/lEVs promoted high antibody levels in B cells cultured with T cell-dependent stimuli by 7 days. In addition, despite the direct inhibitory effect of m/lEVs on early B cell responses, when B cells were cocultured with autologous MDM previously exposed to m/lEVs or m/lEV-ICs, an increased frequency of CD69+ B cells from patients with RA was observed, albeit not with cells from HD. Conclusions: These data together suggest that m/lEVs have a direct modulatory effect in early responses of B cells through B cell receptor that can potentially fail in patients with RA because of the impact of these vesicles over cells of the innate immune system. This phenomenon can potentially contribute to the loss of tolerance and disease activity in patients with RA.